2018
DOI: 10.1016/j.euromechsol.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A new MEMS three-axial frequency-modulated (FM) gyroscope: a mechanical perspective

Abstract: Micro-Electro-Mechanical Systems (MEMS) gyroscopes are inertial sensors for the measurement of angular rates. They have a variety of applications from consumer electronics to drones and the need of stability against environmental fluctuations, such as temperature, is a key factor in order to avoid expensive calibration procedures.Frequency Modulation (FM) has been recently proposed as an innovative working principle for MEMS gyroscopes and as the desired solution in terms of stability against environmental flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Minotti et al [ 67 ] demonstrated a Lissajous frequency-modulated gyroscope with high scale factor stability. The same kind of three-axis Lissajous frequency-modulated gyroscope developed by Zega et al [ 95 ] showed a relatively easy implementation in the roll/pitch axis because it does not require perfect mode matching.…”
Section: Reliability Issuesmentioning
confidence: 99%
“…Minotti et al [ 67 ] demonstrated a Lissajous frequency-modulated gyroscope with high scale factor stability. The same kind of three-axis Lissajous frequency-modulated gyroscope developed by Zega et al [ 95 ] showed a relatively easy implementation in the roll/pitch axis because it does not require perfect mode matching.…”
Section: Reliability Issuesmentioning
confidence: 99%
“…The ambient light sensor can automatically adjust the brightness of the screen according to the ambient illumination. Gyroscopes, accelerometers, GPS, and geomagnetic sensors are also included.…”
Section: Design and Implementation Of The Sewmsmentioning
confidence: 99%
“…Micro-electro-mechanical systems (MEMSs) are smaller in size in comparison with traditional mechatronic systems. They are widely used in medicine, military fields, and our daily life [1][2][3]. They have high requirements in parts, not only small size but also complex microstructures [4,5].…”
Section: Introductionmentioning
confidence: 99%